Extragenic suppression of two ribosomal protein cistrons lying near the rif locus in Escherichia coli. - Molholt, B (1976)
The experiments reported here involve temperature-sensitive mutations in two of five cistrons encoding 50S ribosomal proteins that lie near the rif locus in Escherichia coli. I selected spontaneous TS+ mutants able to grow at elevated temperatures in which the TS+ event takes place outside this tract of cistrons near rif. Six distinct classes of extragenic suppressors were found, five of which have been mapped. Two of these suppressors lie near 64 min, a region known to be rich in cistrons ribosomal proteins (Dennis and Nomura, 1975). The remaining three extragenic suppressors were located near 16.5, 47, and 86 min.